COVID-19 severity and risk of SARS-CoV-2-associated asthma exacerbation by time since booster vaccination: a longitudinal analysis of data from the COVIDENCE UK study - Seif O Shaheen; Adrian R Martineau; Paul E Pfeffer; Mohammad Talaei; Giulia Vivaldi (BMJ Open Respiratory Research)
Background COVID-19 booster vaccinations are offered annually to priority groups, but many people have not been vaccinated in over a year. We therefore assessed the association between time since booster vaccination and breakthrough infection characteristics. We also explored whether incident COVID-19 associates with asthma exacerbations in boosted individuals with asthma and if the risk of COVID-19-associated exacerbation is affected by time since vaccination.Methods COVIDENCE UK is a prospective, longitudinal, population-based study of COVID-19. We included adult participants who had received ≥1 booster vaccination. Time since vaccination was binarised at 6 or 12 months according to vaccine eligibility subgroup. We used regression models to obtain adjusted estimates for the association between time since vaccination and breakthrough infection severity (requiring bedrest vs milder symptoms), symptom duration, and impact on health-related quality of life (EQ-5D-3L Index). We then assessed the association of incident COVID-19 with asthma exacerbations using multilevel mixed models, by time since vaccination.Results 7391 boosted participants reported at least one breakthrough infection. Across all eligibility subgroups, greater time since vaccination associated with increased odds of severe symptoms (ORs ranging from 1.31 (95% CI 1.06 to 1.62) to 1.61 (1.29 to 2.01)). Not receiving a booster vaccination in the previous 12 months was associated with longer time to recovery overall (HR for recovery 0.90, 95% CI 0.81 to 0.99), but evidence for vaccination subgroups was weak. Greater time since vaccination was associated with a small decrease in EQ-5D-3L Index overall (−0.02, 95% CI −0.03 to −0.00) and among participants younger than 75 years, but did not reach our estimates for a minimum clinically important difference. Among 2100 participants with asthma, incident COVID-‍19 associated with increased risk of asthma exacerbation, both within 12 months of vaccination (OR 5.11 (95% CI 4.19 to 6.24)) and later (5.60 (2.98 to 10.53)), with a greater difference in point estimates when considering severe exacerbations (6.59 (4.70 to 9.22) vs 9.20 (3.56 to 23.78)).Conclusion Longer time since booster vaccination consistently associates with more severe infections and may increase the risk of severe asthma exacerbations in people with asthma. These findings highlight the importance of ensuring those currently eligible receive their boosters, and the need for research on further vaccinations in people with asthma no longer eligible for boosters.